2016
DOI: 10.1016/j.exer.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblasts

Abstract: Myofibroblasts are activated in response to tissue injury with the primary task to repair lost or damaged extracellular matrix. Enhanced collagen secretion and subsequent contraction - scarring - are part of the normal wound healing response and crucial to restore tissue integrity. Due to myofibroblasts ability to repair but not regenerate, accumulation of scar tissue is always associated with reduced organ performance. This is a fair price to pay by the body for not falling apart. Whereas myofibroblasts typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
366
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(380 citation statements)
references
References 359 publications
(277 reference statements)
7
366
1
6
Order By: Relevance
“…These showed that P311 stimulated smooth muscle actin production, increased proliferation, promoted migration, and increased contractility of both MFs and HFs, all consistent with induction of the activated state 49 and the transition to myofibroblasts. 50 In addition, P311 had an antiapoptotic effect in both cell types. All these P311-induced changes are consistent with a profibrogenic phenotype and help to understand how P311 contributes to the scar formation.…”
Section: Discussionmentioning
confidence: 95%
“…These showed that P311 stimulated smooth muscle actin production, increased proliferation, promoted migration, and increased contractility of both MFs and HFs, all consistent with induction of the activated state 49 and the transition to myofibroblasts. 50 In addition, P311 had an antiapoptotic effect in both cell types. All these P311-induced changes are consistent with a profibrogenic phenotype and help to understand how P311 contributes to the scar formation.…”
Section: Discussionmentioning
confidence: 95%
“…Detailed reviews on the origin and activation of myofibroblasts are beyond the scope of this review and are given elsewhere (Falke et al 2015;Hinz 2016;Hinz et al 2012;Micallef et al 2012;Postlethwaite et al 2004;van Putten et al 2015). In some tissues, smooth muscle cells, pericytes, and cells derived from epithelial-mesenchymal transformation can also contribute to increased collagen synthesis and collagen deposition in the interstitium Kisseleva and Brenner 2008).…”
Section: Contribution Of Collagen Synthesis To Fibrosismentioning
confidence: 94%
“…Recently, lineage tracing studies in mice have demonstrated that hair-follicle stem cells transiently contribute to wound re-epithelialization by producing cells that migrate to the epithelial layer and differentiate [15]. Beneath the epidermal layer, wound contraction is mediated by the transformation of fibroblasts into contractile myofibroblasts by mechanical signals and TGF-β [16]. Dermal compartment repair is not just mediated by fibroblasts.…”
Section: Proliferationmentioning
confidence: 99%